Two Stay Two Stray Strategy on the Students’ Reading Comprehension: The Effectiveness and the Students’ Perspectives - Haryati Haryati (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2021)
This study was aimed to find out the effectiveness of using Two Stay Two Stray (TSTS) strategy on the students' reading comprehension achievement of the first semester students of English department at Universitas Pamulang, and to know the students’ perspective in applying TSTS. A quantitative approach was conducted in this research by applying Independent T-test calculation. To obtain the data, the writers selected the sample comprised 60 students (30 students in experimental class and 30 students in control class) by having random sampling.  The experimental class was taught by using Two Stay Two Stray (TSTS) strategy and the control class was taught by using conventional method. To collect the data, the writers used two kinds of instruments: a reading test and a questionnaire. These instruments were administered to answer stated research questions. A reading test was used to find out the effectiveness of TSTS strategy by SPSS calculation, and the questionnaire was distributed to find out the students’ perspectives in applying TSTS in reading activity. The research findings indicated the result of hypothesis based on Mann-Whitney U test the Sig 2-tailed value 0.019 < 0.05 which means that the Null Hypothesis (H0) is rejected and Alternative Hypothesis (Ha) is accepted. Therefore, it can be inferred that the Two Stay Two Stray (TSTS) strategy has effectiveness in learning reading comprehension of the students. Furthermore, students assume that Two Stay Two Stray (TSTS) strategy is more enjoyable than the previous strategy (7.7%), they guess the main ideas of the text on the basis of pictures, charts or figures (7,4), and they understand my reading comprehension text before straying to another group (7.3%). Therefore, it shows the Two Stay Two Stray strategy shares the beneficial encouragement on the students reading comprehension.